Connected component masking accurately identifies the ratio of phagocytosed and cell‐bound particles in individual cells by imaging flow cytometry. Issue 4 (12th January 2017) - Fei, Chenjie; Lillico, Dustin M.E.; Hall, Brian; Rieger, Aja M.; Stafford, James L.
Abstract: Innate immune cell‐mediated recognition, capture, and engulfment of large particulate targets such as bacteria is known as phagocytosis. This highly dynamic cellular process involves a series of steps including receptor‐mediated target binding, phagocytic cup formation, pseudopod extension, and phagosome closure, which depend on distinct actin polymerization events. Using flow cytometry, precise determination of target locations relative to cell membranes (i.e., surface‐bound vs. fully engulfed/internalized) during the phagocytic process is difficult to quantify. Here, we describe the application of new analysis features within the IDEAS® software to distinguish internalized and surface‐bound particles on individual cells with a high degree of accuracy and reproducibility. Through the use of connected component masks, the accurate discrimination of surface‐bound beads versus those internalized is clearly demonstrated. In addition, we were able to further analyze the ratio of beads that had been surface‐bound or internalized within individual cells. This novel method of analyzing the phagocytic process provides more accurate determination of target‐cell interactions that will assist in examination of the signalling events that occur during the various stages of phagocytosis. © 2017 International Society for Advancement of Cytometry